Improving performance of inverted organic solar cells using ZTO nanoparticles as cathode buffer layer. (June 2016) - Tsai, Meng-Yen; Cheng, Wen-Hui; Jeng, Jiann-Shing; Chen, Jen-Sue
Highlights: ZTO nanoparticles (NPs) are synthesized via low-temperature solution route. ZTO NPs are utilized as the cathode buffer layer in the P3HT:PCBM solar cells. ZTO NPs buffer layer can improve the device performance to reach a PCE of 2.60%. Abstract: In this study, a low-temperature solution-processed zinc tin oxide (ZTO) films are successfully utilized as the cathode buffer layer in the inverted organic P3HT:PCBM bulk heterojunction solar cells. ZTO film cathode buffer layer with an appropriate Sn-doping concentration outperforms the zinc oxide (ZnO) film with an improved power conversion efficiency (1.96% (ZTO film) vs. 1.56% (ZnO film)). Furthermore, ZTO nanoparticles (NPs) are also synthesized via low-temperature solution route and the device with ZTO NPs buffer layer exhibits a significant improvement in device performance to reach a PCE of 2.60%. The crystallinity of the cathode buffer layer plays an influential factor in the performance. From impedance spectroscopy analysis, a correlation between short circuit current ( J sc ), carrier life time ( τ avg ) and, thus, PCE is observed. The interplay between composition and crystallinity of the cathode buffer layers is discussed to find their influences on the solar cell performance.